Perceptual-Motor Abilities and Reversal Frequency of Letters and Numbers in Children Diagnosed with Poor Reading Skills - Danjela Ibrahimi; Marcos Aviles; Juvenal Rodríguez-Reséndiz (Bioengineering)
Purpose: This paper investigated the visual–perceptual and visual–motor skills and the reversal frequency of letters and numbers that mirror one another in one hundred children aged 6–13 years diagnosed with poor reading skills. Methods: TVPS-4th, VMI-6th, and RFT were performed. Age and sex analysis was carried out. The impact of the eye movement patterns in the perceptual–motor skills and laterality–directionality concepts was also estimated to determine the relationship among tests to predict future results. Results: Most children scored between average and 3 stds below average on the motor VMI-6th test, while half of the participants scored between average and 2 stds below average on TVPS-4th. In the RFT, the majority scored between average and 1.5 stds below average. Participants scored higher on the spatial relationship subtest of the TVPS-4th and lower in the VMI-6th test (<semantics>p<0.001</semantics>). Statistically significant differences were found between the youngest and oldest participants on the TVPS-4th overall performance, as well as VD, FC and VFG skills (<semantics>p<0.05</semantics>). A strong relationship was found between the TVPS-4th and VMI-6th, (<semantics>p<0.001</semantics>). RFT results were different among all groups (<semantics>p<0.05</semantics>). The RFT was better related to the VMI-6th than TVPS-4th; however, it was statistically insignificant. The horizontal component of the DEM test was the best predictor for the TVPS-4th and ratio for the RFT, without attaining statistical significance. No sex differences were found. Conclusions: Results showed that children with poor reading skills exhibit perceptual–motor and reversal frequency difficulties, which are independent of the oculomotor performance. Considering that visual and motor processing are essential elements of the reading and writing process, their evaluation and treatment should be included as part of the multidisciplinary approach for children with poor reading skills. This would boost the general outcome and contribute to their academic achievement.